2009
DOI: 10.1038/ijo.2009.119
|View full text |Cite
|
Sign up to set email alerts
|

Lipomatosis-associated inflammation and excess collagen may contribute to lower relative resting energy expenditure in women with adiposis dolorosa

Abstract: Background Adiposis dolorosa (AD) is a syndrome of obese and non-obese individuals whose hallmark is lipomatosis: unencapsulated painful fatty masses in subcutaneous fat. Lipomatosis may contain excess collagen and multi-nucleated giant (MNG) cells. Case reports suggest metabolic defects in AD. Objectives (1) To determine whether women with AD have altered relative resting energy expenditure (REE per total body mass) compared with controls; and (2) to quantitate lipomatosis-associated collagen, MNGs and tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 48 publications
1
24
0
1
Order By: Relevance
“…Interestingly, pericytes can exert pro-fibrotic activity in that they dedifferentiate into activated fibroblasts producing collagen [55]. Fibroproliferation during hypertrophic scarring might be due to the high sensitivity of pericytes or transdifferentiated myofibroblasts to hypoxic states, resulting in occluded or even partially occluded (micro)vessels [50,56]. …”
Section: Angiogenesis In Skin Wound Healingmentioning
confidence: 99%
“…Interestingly, pericytes can exert pro-fibrotic activity in that they dedifferentiate into activated fibroblasts producing collagen [55]. Fibroproliferation during hypertrophic scarring might be due to the high sensitivity of pericytes or transdifferentiated myofibroblasts to hypoxic states, resulting in occluded or even partially occluded (micro)vessels [50,56]. …”
Section: Angiogenesis In Skin Wound Healingmentioning
confidence: 99%
“…Dr Dercum and others found an infiltration of nerves (neuritis) [185,201] but this has not been substantiated. Increased connective tissue around nerves, blood vessels and as thickened septae has been noted [185,202,203] . Perivascular cells [203] , giant cells [204] , and granulomas suggestive of a foreign body reaction are apparent in some areas [205] .…”
Section: Diagnosismentioning
confidence: 99%
“…These include thyroid dysfunction [185] , pituitary dysfunction, polyglandular disease, infection, neuritis, alcohol, trauma, a defect in the synthesis of long chain fatty acids [205] , lower resting energy expenditure [202] , and altered responses to norepinephrine and insulin. 210 Ballet may have been closest to the actual etiology when he stated that it is a "chronic intoxication of endogenous origin" [211] .…”
Section: Physiology Of Ddmentioning
confidence: 99%
“…Recently, Herbst et al [19] found multinucleated giant cells in three patients with this condition. However, when these patients were compared with healthy obese controls, no differences in the inflammatory reaction were seen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Herbst et al [19] found multi-nucleated giant (MNG) cells in three of the DD patients (n = 5) and in none of the controls (n = 5). Multi-nucleated giant cells are produced by activated, pro-inflammatory macrophages.…”
Section: Introductionmentioning
confidence: 99%